Gas demand in times of crisis: energy savings by consumer group in Germany - Oliver Ruhnau; Clemens Stiewe; Jarusch Muessel; Lion Hirth (ZBW – Leibniz Information Centre for Economics, 2022)
When Russia curbed natural gas supply to Europe in 2021 and 2022, it created a grave energy crisis. This paper empirically estimates the crisis response of natural gas consumers in Germany—for decades the largest export market for Russian gas. Using a multiple regression model, we estimate the response of small consumers, industry, and power stations separately, controlling for the non-linear temperature-heating relationship, seasonality, trends, and economic activity. For industrial consumers, we find a strong and sustained response, with reductions steadily increasing from 4% in September 2021 to 19% in September 2022, roughly following wholesale price levels. For small consumers, including households and small enterprises, we find a response between 10% and 36% from March to September 2022. However, large relative reductions during the summer translate to small absolute values, because small consumers use little gas during this season anyway. The amount of gas burned in power stations is primarily driven by electricity sector events that are not directly linked to reduced Russian gas supply. These findings suggest that voluntary reductions in gas consumption have played a significant role in coping with the crisis.
Older version: https://hdl.handle.net/10419/261082; More recent version: https://hdl.handle.net/10419/266725
Keywords: Q41; 330; Energy demand; Energy crisis; Natural gas; Demand response